Preparation and characterization of low density polyethylene/thermoplastic sago starch/kenaf core fiber composites and their hybrid composites with halloysite clay - Sarifuddin, Norshahida; Ismail, Hanafi; Ahmad, Zuraida (American-Eurasian Network for Scientific Information (AENSI Publisher), 2014)
This present work demonstrated the potential of halloysiteclay (HC) hybridized with kenaf core fibers (KCF) to reinforce the low density polyethylene (LDPE)/thermoplastic sago starch (TPSS) blends. The effects of HC loading (3-15 phr) on the mechanical, thermal and morphological properties were evaluated. The results depicted that Young’s modulus was improved significantly with the inclusion of HCs. A maximum tensile strength of 7.2 MPa was obtained at 12 phr HC loading. Accordingly, the hybrid composites were characterized by Thermogravimetric Analysis (TGA) and Scanning Electron Microscope (SEM). The thermal stability of hybrid composites was found to be enhanced with the addition of HCs. Morphological findings showed that samples containing 12 phr of halloysite clay had better dispersion.